The Concentrations of Interleukin-6, Insulin, and Glucagon in the Context of Obesity and Type 2 Diabetes and Single Nucleotide Polymorphisms in IL6 and INS Genes - Magdalena Król-Kulikowska; Iwona Urbanowicz; Marta Kepinska (Journal of Obesity)
Obesity and diabetes are a problem of modern medicine. Although the environmental factors contributing to the development of these diseases are widely known, research into genetic factors is still ongoing. At the same time, the role of inflammation in the pathophysiology of obesity and diabetes is increasingly emphasized. Therefore, the purpose of this study was to investigate the influence of two selected polymorphisms (rs1800795 and rs3842729) on the development of obesity and type 2 diabetes. In this study, 118 participants were examined, including a control group (nonobese and nondiabetic group), an obese group, and a diabetic group. Genotype analysis was performed using the PCR-RFLP method. It has been shown that in patients with the G/G genotype within the rs1800795 polymorphism (IL6), the chance of developing type 2 diabetes is several times lower compared to patients with the G/C and C/C genotypes. However, the rs3842729 polymorphism (INS) does not directly affect the risk of obesity or type 2 diabetes (T2D), although elevated insulin concentrations have been observed in obese and diabetic patients. These results confirm the impact of the rs1800795 polymorphism on the development of diabetes; however, this relationship is more complex and requires further research on other factors.